Multifaktorial Pemicu Cancer-Related (CRF) Pada Pasien Kanker - Yesiana Dwi Wahyu Werdani; Maria Theresia Arie Lilyana; Tiffani Aditya Wijono Putri (JURNAL NERS LENTERA, 2022)
Cancer related Fatigue (CRF) is a symptom that occurs in almost all cancer patients. CRF causes various physical and psychological impacts that can hinder the patient's normal life. The aim of this study was to explain the multifactorial triggers of CRF in cancer patients. The research design used is a descriptive design. The population of all cancer patients at the Kedungdoro Public Health Center Surabaya, with a large sample of 28 people. Samples were taken by purposive sampling based on inclusion criteria. The instrument uses a Brief Fatigue Inventory (BFI) which has been tested for validity and reliability. The triggering factor for CRF in this study with the highest CRF score for each factor was age in the elderly group (23.4 + 6.8), gender factor was found in women (18.96 + 6.73), the type of cancer was found in breast cancer (21.25 + 7.36), the cancer stage factor was in stage 3 cancer (24.11 + 8.29), the length of cancer was 4-6 years (21.62 + 6.04), and the cancer therapy factor was found in respondents who received chemotherapy + surgery therapy (24.11 + 8.29). All of the above factors trigger mild CRF with varying mean scores ranging from the lowest score of 16 to the highest score of 24.11. CRF does not appear only because of cancer, but there are other multifactorial factors that trigger CRF in cancer patients